Civil Society in Zambia: Limits to Growth - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
'There has been an explosive growth in organisations registering as Societies since the creation of the Third Republic in 1991. Many of these are formed by ex-civil servants whose positions have been eliminated in the scaling down of state...